THEORETICAL JUSTIFICATION OF FACTORS OF INFLUENCE ON FUEL CONSUMPTION OF DUMP TRUCKS IN THE PROCESS OF UNLOADING BULK CARGO (World Science, 2022)
This article presents the results of the analysis of the study of the working process of dump trucks and the factors that affect the fuel consumption of dump trucks in the process of unloading bulk cargo, with further development of principles and methods for determining optimal (rational) modes of dump trucks. specialized equipment, ensuring minimum fuel consumption and harmful emissions into the atmosphere and maximum productivity when performing dump trucks transport and specialized work.During the study, the factors that directly affect the amount of fuel consumption during the unloading of the dump truck platform were comprehensively substantiated. The cost of unloading bulk cargo is set. The platform of the dump truck is loaded in three ways of placing the cargo on the platform (the center of gravity of the cargo is located on the front of the platform, the center of gravity of the cargo is located on the center of the platform, the center of gravity is located on the back of the platform).Unloading was carried out at the set speed of the crankshaft of the dump truck engine (at 1500 min-1, at 2000 min-1, at 2500 min-1) for three ways of loading the platform. According to the analysis of literature sources and research, we can conclude that the operational factor – is one of the main factors on which depends on the productivity of transport work by dump trucks, and which accounts for the largest percentage of fuel and energy resources. Unloading rate (Qroz) is one of the main indicators that is taken into account when calculating fuel consumption for transport work by dump trucks. But to determine the fuel consumption of a dump truck in the unloading process is much more difficult, because a clear rate of fuel consumption for this process is not defined in it, as this indicator is an individual and complex characteristic.